Morphological study of the gastrointestinal tract around the ligament of Treitz using upper gastrointestinal radiography: Fundamental data for EUS‐guided gastrojejunostomy. (16th July 2021) - Nutahara, Daisuke; Nagai, Kazumasa; Sofuni, Atsushi; Tsuchiya, Takayoshi; Ishii, Kentaro; Furuichi, Yoshihiro; Kitamura, Katsuya; Itoh, Masahiro; Miyazawa, Hideaki; Itoi, Takao
Abstract: Background/Purpose: We developed EUS‐guided double‐balloon occluded gastrojejunostomy (EPASS) for gastric drainage tract obstruction. The success of EPASS depends on the proximity of the stomach and the gastrointestinal (GI) tract near the ligament of Treitz. The aim of this study is to clarify the GI anatomy near the ligament of Treitz. Methods: One thousand and sixteen cases imaged upper GI radiography using barium were retrospectively evaluated. Morphologically, the GI tract running near the ligament of Treitz was divided in three types: Type I: The 4th portion of the duodenum (D4) approaches the stomach; Type II: D4 does not approach the stomach; Type III: D4 forms a loop to the jejunum. The minimum distance between the stomach and the GI tract near the ligament of Treitz was measured. Results: Based on the morphological classification, 74.6% in the study group was classified in Type I, 22.0% in Type II, and 3.3% in Type III, respectively. The median minimum distance in Type II/III group were significantly longer, compared with the Type I ( P < .01). Conclusions: The GI anatomy near the ligament of Treitz was clarified using upper GI radiography. It is divided into three patterns, and one‐fourth of cases may have difficulty in EUS‐guided gastrojejunostomy. Abstract : Highlight Nutahara and colleagues identified three morphological patterns of the gastrointestinal (GI) tract near the ligament of Treitz on upper GI radiography. The minimum distance between the stomach and the GI tract was significantly longer in Types II/III than in Type I. These data could be useful for EUS‐guided double‐balloon occluded gastrojejunostomy.